An expanding high velocity hi cloud probably ejected from the galactic nucleus - Mirabel Miquele, Igor Félix (1976)
An object located approximately atl=8°,b=−4° with a mean radial velocity of −212.3 km s−1 has been observed in the 21 cm neutral hydrogen line. The mean weighted velocity dispersion is 11.2 km s−1 and the total mass is estimated to be 190R2 (kpc) solar masses. We discuss possible interpretations of the origin and nature of this object. The most likely interpretation is that we observe an expanding object which has been ejected from the galactic nucleus.